Answer:
(9, -4)
Explanation:
Given the general equation of a circle to be x²+y²+2gx+2fy+c = 0 where the coordinates of the centre is give as (-g,-f)
Given the equation of the circle
(x – 9)² + (y + 4)² = 1
First, we need to expand the equation and write it in its standard form as shown above to have;
x²-18x+81+y²+8y+16 = 1
x²+y²-18x+8y+16-1 = 0
x²+y²-18x+8y+15 = 0
Comparing the resulting equation to the general equation above to get g and f,
2gx = -18x
2g = -18
g = -9
Similarly,
2fy = 8y
2f = 8
f = 4
The circle centre of the circle (-g,-f) = (9,-4)